THE IMPLEMENTATION OF THE AUTHORITY OF MANDATORY GOVERNMENT AFFAIRS RELATED TO BASIC SERVICES IN THE PROVINCE OF WEST JAVA YEAR 2014-2017 - Deliarnoor, Nandang Alamsah (Advances in Social Sciences Research Journal, 2018)
Law No. 23 of 2014 about regions that government affairs are divided into absolute affairs, concurrent connections affairs and general government affairs. Concurrent affairs are joint affairs that are divided into the authority of the central, provincial and regional governments and become the basis of the implementation of local autonomy. The purpose of this research is to examine the implementation of the authority of the government in administering concurrent connections affairs, especially mandatory affairs related to basic services. This research method utilizes qualitative approach and to examine normative jurisdiction. This research reveals that whilst the implementation of local autonomy for 13 years has brought forth a number of positive changes to the community, it still lacks in both regulations and its implementation. One of the aspects that need to be addressed and clarified is the limitation of the authority of government given to provinces and regions.